Determinants of Supply Chain Mangament Factors in the Commersial Banks (Indonesian IDX Case Study) - Gusganda Suriamanda; Disman Disman; Nugraha Nugraha; MW Zarkasyi (International Journal of Supply Chain Management, 2020)
Abstract- This study is aimed at analyzing the predictor variables used to predict the performance of banks listed on the Indonesia Stock Exchange, from 2000 to 2017 by using supply chain strategies. The predictor variables used in this research are as follows: Operational Income Operational Costs (BOPO), Market Ratio of Earning Per Share (Share EPS), Net Interest Margin (NIM), Non-Performing Loan (NPL), Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR). While the financial performance was measured using Return On Assets (ROA) with panel data analysis used to examine the model. The results showed that Operational Costs Operating Income (BOPO), Market Ratio of Earning Per Share (EPS), Net Interest Margin (NIM), Non-Performing Loan (NPL), Capital Adequacy Ratio (CAR), and Loan to Deposit Ratio (LDR), simultaneously affected the Return On Assets (ROA) of banks listed on the IDX. It was also able to cover the gaps of previous researches by extending the research time and multiplying predictor variables used in detecting banking performance. The study concluded there is a positive strong relationship between performance and the independent variables as shown by the Pearson?s co-efficient correlation which is significant as indicated by the P-value at 95% level of confidence. There are various determinants of supply chain performance that contributes to efficient and effective performance of supply chain in the organization namely ICT, knowledge and information sharing, trust, culture and joint decision making